DAMPAK PEMBERLAKUAN OMNIBUS LAW TERHADAP STATUS PEKERJA MIGRAN INDONESIA SEBAGAI SUBJEK PAJAK LUAR NEGERI - Indra Gunawan (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2026)
This study aims to analyze the impact of the Omnibus Law on the status of Indonesian Migrant Workers (PMI) as Foreign Tax Subjects (SPLN), as well as its implications for legal certainty and the potential for double taxation. Changes in tax regulations arising from policy reforms through the Job Creation Law have created new dynamics in determining the tax subject status of Indonesian citizens working abroad. This situation requires a comprehensive legal study to understand how these regulations affect PMI's tax obligations and the legal protection provided by the state. The research method used is normative legal research with a statute approach and a comparative law approach. The data sources used are primary, secondary, and tertiary legal materials analyzed qualitatively. Primary legal materials include the Law on General Provisions and Tax Procedures, the Income Tax Law, Law Number 11 of 2020 concerning Job Creation, and Minister of Finance Regulation Number 18/PMK.03/2021, which regulates the criteria for determining SPLN status for Indonesian citizens working abroad. An analysis was also conducted by comparing regulations before and after the policy change to assess the consistency of norms and their implications for tax compliance. The results show that the enactment of the Omnibus Law brought changes to the mechanism for determining the tax status of migrant workers and clarified the criteria for determining SPLN. However, in practice, several administrative obstacles remain, limited understanding of regulations by migrant workers, and the potential risk of double taxation due to differences in tax systems between countries. Therefore, policy harmonization, increased tax outreach to migrant workers, and strengthened coordination between the Directorate General of Taxes and migrant worker protection agencies are needed to ensure legal certainty and fiscal justice for migrant workers working abroad.